‘I’m just sort of hoping that nothing like that would happen here’: menstrual tracking apps, data and risk in Aotearoa New Zealand - Anna Friedlander; Johanna M. Schmidt; Charlotte Greenhalgh; Holly Thorpe (Kōtuitui, 2025)
Menstrual tracking apps (MTAs) are popular apps used to track menstruation, ovulation and a wide range of embodied experiences. They can hold comprehensive repositories of years of data about users’ health and lives. This data may be utilised by a range of parties in commercial, research, or other applications, in operations largely opaque to the MTA user. This paper draws on solicited diaries and interviews with 13 MTA users in Aotearoa to examine perceptions of data risk. Participants held a range of positions. Some considered their data to be largely risk-free, at least some of the time. Other participants did perceive risks in menstrual data. Sometimes participants contextualised risk with respect to reproductive health policy: some perceived this risk as mainly or only affecting menstruators overseas; while others imagined potential future risks for menstruators in Aotearoa. One participant discussed data risk with respect to rangatiratanga and mana motuhake (self-determination). This paper contributes to a growing body of international research that examines MTA users’ perceptions of risk in a rapidly changing world.